Isolation of Chlamydia trachomatis from throat and rectum of homosexual men. Issue 3 (June 1977) - Goldmeier, D.; Darougar, S.
Abstract : Isolation of Chlamydia trachomatis is reported from homosexual men: from the throat with no abnormal symptoms and from the rectum in two cases of proctitis.